Implementasi Surat Keputusan Kepala Dinas Pendidikan dan Kebudayaan Kabupaten Sidoarjo Nomor 188/456/438.5.1/2021 Tentang Penetapan Tim Pelaksana Sekolah Ramah Anak Jenjang Sekolah Dasar Di Kabupaten Sidoarjo Tahun 2021 (Studi Kasus SDN Ganting) - Ratna Yunitasari; M. Kendry Widiyanto; Dida Rahmadanik (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Child-Friendly Schools are essentially schools that provide all children with full rights, as well as classroom and school management that must be supported by positive physical, psychological, social, healthy and safe conditions. Child-Friendly Schools are also an ideal concept for school-aged children. This program is related to the Child Friendly Regency/City launched by the government. The aim of developing Child Friendly Schools is to prevent violence against children and other school residents, prevent children from getting sick due to food poisoning and an unhealthy environment, prevent accidents in schools caused by infrastructure or natural disasters, prevent children from becoming smokers, alcohol drinkers and users. NAPZA, creates good relationships between school members, makes it easier to monitor children's conditions while they are at school, and makes it easier to achieve educational goals.